Passenger's satisfaction toward service quality at Melaka International Airport (MIA) / Siti Nurfatin Mohammad Fadzilah , Nor Faezah Mohd Radzi and Margret Neri Peter - Mohammad Fadzilah, Siti Nurfatin; Margret Neri Peter (Faculty of Hotel and Tourism Management, 2014)
This chapter illustrates the general description of this study. It started with the background of the study which expressed the SERQUAL dimensions towards passenger satisfaction. Next, the identification of research issues was organized in the problem statement. From there, the research objectives, research questions and theoretical framework were developed and presented accordingly. Lastly, the researcher discussed about the significance of the study and its contribution towards management of Malacca International Airport, academician as well as the passengers.